A multicentre study of antifungal susceptibility patterns among 350 Candida auris isolates (2009–17) in India: role of the ERG11 and FKS1 genes in azole and echinocandin resistance. (9th January 2018) - Chowdhary, Anuradha; Prakash, Anupam; Sharma, Cheshta; Kordalewska, Milena; Kumar, Anil; Sarma, Smita; Tarai, Bansidhar; Singh, Ashutosh; Upadhyaya, Gargi; Upadhyay, Shalini; Yadav, Priyanka; Singh, Pradeep K; et al.
Abstract: Background: Candida auris has emerged globally as an MDR nosocomial pathogen in ICU patients. Objectives: We studied the antifungal susceptibility of C. auris isolates ( n = 350) from 10 hospitals in India collected over a period of 8 years. To investigate azole resistance, ERG11 gene sequencing and expression profiling was conducted. In addition, echinocandin resistance linked to mutations in the C. auris FKS1 gene was analysed. Methods: CLSI antifungal susceptibility testing of six azoles, amphotericin B, three echinocandins, terbinafine, 5-flucytosine and nystatin was conducted. Screening for amino acid substitutions in ERG11 and FKS1 was performed. Results: Overall, 90% of C. auris were fluconazole resistant (MICs 32 to ≥ 64 mg/L) and 2% and 8% were resistant to echinocandins (≥8 mg/L) and amphotericin B (≥2 mg/L), respectively. ERG11 sequences of C. auris exhibited amino acid substitutions Y132 and K143 in 77% ( n = 34/44) of strains that were fluconazole resistant whereas WT genotypes, i.e. without substitutions at these positions, were observed in isolates with low fluconazole MICs (1–2 mg/L) suggesting that these substitutions confer a phenotype of resistance to fluconazole similar to that described for Candida albicans . No significant expression of ERG11 was observed, although expression was inducible in vitro with fluconazole exposure. Echinocandin resistance was linked to a novel mutation S639F in FKS1 hot spot region I. Conclusions: Overall, 25% and 13% of isolates were MDR and multi-azole resistant, respectively. The most common resistance combination was azoles and 5-flucytosine in 14% followed by azoles and amphotericin B in 7% and azoles and echinocandins in 2% of isolates.